Insect succession associated with a hanging pig carcass placed in an oil palm plantation in Malaysia - Heo, Chong Chin; Sallehudin Sulaiman,; Hidayatulfathi Othman,; John Jeffery,; Hiromu Kurahashi, (Universiti Kebangsaan Malaysia, 2010)
This study was carried out in an oil palm plantation in Tanjung Sepat, Selangor in September 2007 by using pigs (Sus scrofa L.) as a carcass model in a forensic entomological research. A 2.5 month old pig (10 kg) which died naturally was hanged on a palm tree to observe the insect succession and decomposition stages. Observation was made for 16 days; one afternoon visit per day and all climatological data were recorded. On the first day, adult muscids of Ophyra spinigera Stein and Musca domestica L. were observed, however no blowfly (Calliphoridae) activities were sighted. Fly eggs wer seen on the second day on both sides of the face, inside nostrils and genitourinary area. Adults of Chrysomya megacephala Fabricius and Chrysomya rufifacies (Macquart) congregated on the head and anal areas. Adult flies and maggots (first and second instars) were observed in the mouth and anus of the pig on the third day of hanging. Adult yellow jackets (Vespidae) and spiders (Arachnida) were found preying on some adult flies. Rove beetles (Staphilinidae) were also discovered on the pig carcass. Only a few ants (Formicidae) were sighted. Maggot masses were found in eye orbits, neck, and genital organs on the fourth day of hanging and some maggots were seen falling down to the ground. The dominant maggot species identified on this day was Ch. megacephala. On the sixth day, the head, neck, and anus were in the stage of active decay. Maggots of Ch. rufifacies were abundant on the seventh day and was the dominant species. On day eight the carcass fell onto the ground. Chrysomya rufifacies maggots were found underneath the pig carcass and they started to migrate and pupated under the soil. On the tenth day, third instar Op. spinigera maggots were found under the carcass. The rate of carcass decomposition slowed down and became stable from tenth day onwards to the sixteenth day of decomposition. Thereafter, most of the remaining parts of the body remained dried and devoid of any insects.